Implementation of Green Curriculum in Vocational Education: A Preliminary Study in Vocational High Schools (SMK) in Malang City - Novia Nailatun Nufus; Purnomo Purnomo; Eddi Sutadji (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The increasing demand for sustainability-oriented competencies has encouraged vocational education institutions to integrate green curriculum principles into teaching and learning practices. This study aims to examine the implementation of the green curriculum in vocational education and identify institutional challenges in supporting sustainability integration. A descriptive quantitative approach with an exploratory design was employed. Data were collected using a 15-item Likert-scale questionnaire administered to four Heads of Fashion Design Study Programs from four vocational high schools (SMKs) in Malang City, Indonesia. The findings indicate that green curriculum implementation is generally at a high level, particularly in curriculum integration, instructional practices, and facilities supporting sustainability. However, teacher capacity development, alignment with green industry requirements, and evaluation systems remain only moderately implemented, indicating an implementation gap between pedagogical practices and institutional readiness. The study contributes to the literature by conceptualizing green curriculum implementation as a multidimensional institutional process rather than merely a pedagogical innovation. Nevertheless, the findings should be interpreted with caution because the study involved only four participants and was designed as an exploratory investigation, limiting the generalizability of the results. Future studies are recommended to involve larger samples and diverse vocational education sectors to strengthen empirical evidence.